2021
DOI: 10.1002/pssa.202000550
|View full text |Cite
|
Sign up to set email alerts
|

A Laser‐Processed Silicon Solar Cell with Photovoltaic Efficiency in the Infrared

Abstract: Hyperdoped and textured silicon created with a femtosecond laser in the presence of SF 6 gas has a highly absorbing surface with extended spectral sensitivity in the infrared. The main drawback of this micro-and nanostructured material for photovoltaic (PV) cells is an increase in charge-carrier recombination at the surface due to the typically poor crystallinity of the surface layer. Laser annealing postprocessing of the black silicon (b-Si) surface is used to greatly reduce the crystal structure defects whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Similarly, for solar cell application, Sánchez et al showed the highest absorptance in broadband wavelengths (400–2500 nm) with a laser fluence of 5 kJ m −2 , which resulted in increased photovoltaic efficiency due to extra gain from intermediate states in NIR. [ 13 ] Although the tailored optical and electrical properties in our experiment are obtained in the absence of high sub‐band gap absorption, the optimal laser fluence obtained in our work may also be applicable to fs‐bSi after hyperdoping. In conclusion, the similar fluence used in different work suggests that the laser fluence is a key parameter to achieve high performance devices despite doping or post processing.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, for solar cell application, Sánchez et al showed the highest absorptance in broadband wavelengths (400–2500 nm) with a laser fluence of 5 kJ m −2 , which resulted in increased photovoltaic efficiency due to extra gain from intermediate states in NIR. [ 13 ] Although the tailored optical and electrical properties in our experiment are obtained in the absence of high sub‐band gap absorption, the optimal laser fluence obtained in our work may also be applicable to fs‐bSi after hyperdoping. In conclusion, the similar fluence used in different work suggests that the laser fluence is a key parameter to achieve high performance devices despite doping or post processing.…”
Section: Resultsmentioning
confidence: 96%
“…[ 10,11 ] Thus, the fs‐bSi has a high promise in applications that benefit from broadband responsivity extending from UV to IR such as photodetectors and solar cells. [ 12,13 ]…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the reflectivity and the dielectric function, we can deduce that a femtosecond laser can perform an ultrafast optical change while the Ge thin film is still cold, offering new possibilities for a wide range of Ge applications at both the micro- and nano-scale, in the same way that other semiconductors are utilized currently. For instance, direct femtosecond laser writing applied to Si [ 35 , 36 ], diamond [ 37 , 38 , 39 ], and SiC [ 40 , 41 ] has indeed been shown to significantly increase the photon absorption of the materials in the solar spectrum, allowing for the fabrication of innovative high-performance solar cells [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hyperdoped systems achieved using this doping method more often use fs-lasers. The dopants investigated included S, Se, Te, Cr, and Mo [1,7,38,[62][63][64][65][66][67][68][69]. There are differences in the laser-matter interaction with different phases of the dopant precursor (gaseous or solid, particularly when multiple laser pulses and scanning are employed) [70].…”
Section: Thin-film or Gas Phase Dopant Precursormentioning
confidence: 99%